PENGARUH VOLUME OFFER SAHAM TERHADAP HARGA SAHAM (STUDI EMPIRIS PADA SAHAM-SAHAM JAKARTA ISLAMIC INDEX DI BURSA EFEK INDONESIA PERIODE JANUARI – APRIL 2020) - -, Sunaryo (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2020)
The purpose of this research was to determine the influence of offering volume stock on the stock price. This research sample is shared in the sharia category in the JII group (Jakarta Islamic Index) listed on the Indonesia Stock Exchange (IDX) period January-April 2020 by using a saturated sampling method. There were 20 stocks selected as samples. The research method used in this research is panel data regression. The results of the study showed that the offer volume stock has a significant and negative influence on the stock price.